Dorsal-ventral patterning of the spinal cord requires Gli3 transcriptional repressor activity - Persson, Madelen (Cold Spring Harbor Laboratory Press, 2002)
Sonic hedgehog (Shh) plays a critical role in organizing cell pattern in the developing spinal cord. Gli proteins are thought to mediate Shh signaling, but their role in directing neural tube patterning remains unclear. Here we identify a role for Gli3 transcriptional repressor activity in patterning the intermediate region of the spinal cord that complements the requirement for Gli2 in ventral regions. Moreover, blocking all Gli responses results in a complete dorsalization of ventral spinal cord, indicating that in addition to the specific roles of Gli2 and Gli3 in the neural tube, there is functional redundancy between Gli proteins. Finally, analysis of Shh/Gli3 compound mutant mice substantiates the idea that ventral patterning may involve a mechanism independent, or parallel, to graded Shh signaling. However, even in the absence of graded Shh signaling, Gli3 is required for the dorsal-ventral patterning of the intermediate neural tube. Together these data raise the possibility that Gli proteins act as common mediators integrating Shh signals, and other sources of positional information, to control patterning throughout the ventral neural tube.